Influence of familiarity with goat meat on liking and preference for capretto and chevon. (August 2015) - Borgogno, Monica; Corazzin, Mirco; Saccà, Elena; Bovolenta, Stefano; Piasentier, Edi
Abstract: The research aimed at assessing liking and preference for capretto and chevon as a function of consumer familiarity with goat meat. Five meats were produced: traditional milk capretto (MC), heavy summer capretto (HSC), summering (SCh), fall (FCh) and late fall chevon (LFCh). HSC was the most tender meat, having less cooking losses than both MC and redder chevon types. The instrumental profile corresponded with the appearance and texture attributes perceived by panellists. With aging of kids, meat lost its milk aroma (MC) and sweet taste (HSC) and acquired an increasing intensity of goat flavour and livery notes, partially related to feeding regime and fatty acid profile. A niche market preferred chevon over capretto, while the cluster of consumers who were unfamiliar with chevon showed a decrease in pleasantness when tasting chevon, the familiar group reduced their ratings only for meat from the oldest kids. Highlights: Capretto has delicate sensory properties, like tenderness, juiciness and sweetness. Chevon became progressively redder, goaty in flavour and tougher with age. A niche of one-quarter of consumers preferred chevon over capretto. Unfamiliar consumers showed a decrease in pleasantness when tasting chevon. Familiar consumers reduced liking only for chevon from kids close to puberty.